Teacher Career Management Transformation: Enhancing Professional Growth Through Digitalization - Hasan Baharun; Asrani Asrani (Al-Qalam Institue, 2024)
Digital transformation in teacher career management has become an urgent need with the rapid development of information technology. In the face of globalization challenges, technological adaptation in education, particularly in managing teacher careers, is crucial for enhancing the quality and professionalism of educators. This article aims to analyze the implementation of digital tools in teacher career management at MA Nurul Jadid, focusing on the use of e-portfolios, Learning Management Systems (LMS), and Digital Personnel Information Systems. This research employs a qualitative approach with data collection techniques of interviews and documentation, as well as thematic analysis. The findings reveal that the application of digital tools improves career management efficiency, accelerates performance evaluation, and supports data-driven career planning. Despite challenges in digital literacy and infrastructure, the use of technology successfully strengthens teacher professionalism. In conclusion, digital transformation plays a significant role in teacher career development, with recommendations to enhance digital training and improve supporting infrastructure. Future research may explore the psychological and motivational factors influencing teachers' adoption of technology.